Visitors' Perceptions of Cultivation Technology Innovation in Agro Innovation Park, BPTP Jambi. Issue 1 (March 2021) - Edi, S; Rustam,
Abstract: Agro Innovation Park is a forum for developing various superior technologies from the Agricultural Research and Development Agency. The services provided are complemented by a library, a consultation area, a training arena, and a playground. This study aims to determine visitors' perceptions of several technological innovations implemented. The data presented are in the form of park arrangement, various technological innovations, number of visitors, perceptions of visitors, and apprentices in 2018, 2019, and 2020. The Agro Innovation Park is located in Sungai Tiga IP2TP office area, Pondok Meja Village, Mestong District, Muaro Jambi Regency, Jambi Province. This park was built in 2015, having several types of plants with various adaptive and innovative technologies, ranging from short-lived plants such as leaf-producing vegetables, medium-aged plants such as fruit-producing vegetables, and long-lived plants such as perennials, and also equipped with medicinal plants. There was an increase in the number of visitors and internship students from 2018 to 2019, but there was a decline afterward. This happened due to the Covid-19 pandemic resulting in the temporary closure of parks for visitors and apprentices. The findings indicate that In terms of the service provided, 20% of the visitors were satisfied and 80% said that they were very satisfied. For the various technological innovations implemented, 88% of the visitors stated that they were very interested in park management and 75% were very interested in hydroponic technology innovations.